2000
DOI: 10.1590/s0006-87052000000100016
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de regressão não-linear aplicado ao estudo da estabilidade fenotípica de genótipos de feijão no Estado do Paraná

Abstract: RESUMOO presente trabalho teve por objetivo estudar a estabilidade fenotípica da produtividade de grãos de feijão (Phaseolus vulgaris L.) com dados obtidos no Ensaio Regional Final do Estado do Paraná, durante o ano/safra 1996/97, através de modelo não-linear, (nos parâmetros propostos por Toler), assim expresso: Yij = αi + [Zjβ1i + (1 -Zj) β2i] µj + εij. Esse autor propôs testes das hipóteses H(β1i = β2i) e H(β1i = β2i = βi = 1), as quais permitem enquadrar os genótipos em cinco grupos, conforme o padrão de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 8 publications
0
16
0
7
Order By: Relevance
“…Various genotypes showed a good fit to the bi-segmented Toler model (1990) (H 0 : β 1i ≠ β 2i ), with doubly desirable responses (β 1i < 1 <β 2i ) and good predictability of performance (r > 0.84): for FLOW, CMSXS629, CMSXS637, and CMSXS648; for GMY, BR505, BR507, CMSXS630, CMSXS633, CMSXS636, and CMSXS637; for TSS, BR505 and BRS601; for TBH, BRS506, BRS511, and CMSXS648 (Table 2). In this context, Rosse and Vencovsky (2000) suggested that the major problem faced by breeders is to identify a productive genotype with doubly desirable responses. For instance, for GMY, only the genotypes in group A (BR505, BR507, and CMSXS630) were categorized with statistical significance as best adapted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various genotypes showed a good fit to the bi-segmented Toler model (1990) (H 0 : β 1i ≠ β 2i ), with doubly desirable responses (β 1i < 1 <β 2i ) and good predictability of performance (r > 0.84): for FLOW, CMSXS629, CMSXS637, and CMSXS648; for GMY, BR505, BR507, CMSXS630, CMSXS633, CMSXS636, and CMSXS637; for TSS, BR505 and BRS601; for TBH, BRS506, BRS511, and CMSXS648 (Table 2). In this context, Rosse and Vencovsky (2000) suggested that the major problem faced by breeders is to identify a productive genotype with doubly desirable responses. For instance, for GMY, only the genotypes in group A (BR505, BR507, and CMSXS630) were categorized with statistical significance as best adapted.…”
Section: Resultsmentioning
confidence: 99%
“…In the model, the imposed restrictions are required so that the average performance of genotypes takes place with = 0 in the scale of environmental effects and that their response to the average sensitivity is equal to unit (Rosse and Vencovsky, 2000).…”
Section: (Equation 1)mentioning
confidence: 99%
“…The calculation of R 2 corresponded to the square of the correlation coefficient estimated from the values observed for the hybrids and the values estimated through the non-linear model for stability (Rosse and Vencovsky 2000).…”
Section: Methodsmentioning
confidence: 99%
“…It allows the classification of hybrids under various groups, thus making it a promising method for the study of adaptability and stability. This method has been used to study crops such as beans (Rosse and Vencovsky 2000), sugarcane (Rosse et al 2002), eucalyptus (Nunes et al 2002), melon (Nunes et al 2006) and soybean (Morais et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos métodos de análise de adaptabilidade e estabilidade foram propostos na literatura (Eberhart & Russel, 1966;Lin & Binns, 1988;Crossa, 1990;Gauch & Zobel, 1996;Magari & Kang, 1997;Toler & Burrows, 1998;Rosse & Vencovsky, 2000). Segundo Cruz & Regazzi (2001), alguns métodos são alternativos, enquanto outros são complementares, e podem ser utilizados conjuntamente.…”
Section: Introductionunclassified